A comprehensive study on epigenetic signatures to monitor disease progression and the response to therapy in breast cancer - Dhruv Parikh; Manan Shah (Biomedical Analysis)
Breast cancer is the single most complex cancer type, affecting thousands around the globe annually. With the recent studies highlighting epigenetic signatures in breast cancer detection, this landscape can be exploited to inhibit breast cancer potentially. This paper comprehensively explores epigenetic signatures in breast cancer, elucidating their impact on disease progression and therapeutic responses. The objective is to unravel the intricate interplay of different epigenetic biomarkers in shaping breast cancer's molecular landscape. We delve into the diverse manifestations of epigenetic alterations, particularly in the context of breast cancer heterogeneity, offering insights into early diagnosis, prognosis assessment, and targeted therapeutic strategies. The discussion encompasses the dynamic role of epigenetic changes in influencing gene expression, tumor characteristics, and treatment outcomes across various breast cancer subtypes. The paper underscores the transformative power of incorporating epigenetic evaluations into breast cancer clinical care, facilitating a personalized approach. Notably, emphasizing the need for precision, combination therapies, and the development of robust epigenetic biomarkers. By examining recent technological advancements, such as single-cell RNA sequencing and next-generation sequencing, we uncover the intricate molecular landscapes underpinning breast cancer heterogeneity and resistance mechanisms. We also address the challenges faced by current epigenetic therapies, such as DNA methyltransferase inhibitors and histone deacetylase inhibitors, and the need for precision in their application. In summary, this paper unfolds a compelling narrative that advances our understanding of epigenetic signatures in breast cancer, offering a beacon of hope for improved patient outcomes through targeted and personalized therapeutic interventions.